E-185 MR vessel wall imaging in the diagnosis of occult ruptured blister intracranial aneurysms. (4th August 2020) - Moazeni, Y; Abdalla, R; Sukumaran, M; Cantrell, D; Shaibani, A; Hurley, M; Jahromi, B; Potts, M; Ansari, S
Abstract : Purpose: Blister intracranial aneurysms are a rare etiology of subarachnoid hemorrhage (SAH) accompanied by high morbidity and mortality rates. Digital subtraction angiography (DSA) and CT angiography (CTA) serve as the main imaging techniques for diagnosing the cause of SAH, yet blister aneurysms can remain occult on DSA or CTA imaging due to their small size, broad based morphology, and early transient thrombosis. In this case series of SAH patients that were diagnosed with ruptured blister aneurysms, we investigated the role of high-resolution (HR)-MRI Vessel Wall Imaging (VWI) in identifying culprit, ruptured aneurysm diagnoses. Methods and Materials: We performed an IRB-approved retrospective review of patients diagnosed with SAH from 2010–2019 at our institution. We studied patient demographics, presentations, aneurysm size/locations, initial and follow-up imaging including CT, CTA/MRA, DSA, and MR VWII studies. Results: Seven patients (1 Male: 6 Female, mean age: 52) with ruptured blister aneurysms were identified. Median of Hunt-Hess grade (range: 1–4) and Fisher grade (range: 2–4) at presentation were 1 and 3 respectively. Blister aneurysm were small 1–3 mm in mean size and broad based neck morphology in the anterior circulation. All but 2 of them were located in non-branching sites. Initial CTA was diagnostic for a ruptured blister aneurysm in 3/7 (43%), confirmed with DSA. In the remaining 4/7 cases CTA was negative, and DSA identified two of these occult ruptured blister aneurysm initially and two subsequently on 1 week follow-up DSA. HR-MR VWI was performed in 3/4 patients 1–3 days after presentation and revealed mild to moderate focal enhancement and/or T1 hyperintensity of the small aneurysm wall corresponding to the blister aneurysm sites confirmed by initial or follow-up DSA. Conclusion: HR-MR VWI can provide adjunctive diagnostic information for the identification of occult ruptured blister aneurysm in SAH patients, when combined with conventional imaging studies such as CTA and DSA. HR-MR VWI may assist in accelerate the time to definite diagnosis in cases with negative initial CTA or DSA findings. Disclosures: Y. Moazeni: None. R. Abdalla: None. M. Sukumaran: None. D. Cantrell: None. A. Shaibani: None. M. Hurley: None. B. Jahromi: None. M. Potts: None. S. Ansari: None.